Exploring Power Dynamics in Sally Rooney’s ’Normal People’ - Wardyah Ningrum (Morphosis: Journal of Literature, 2024)
This study entitled “The Portrayal of Power Relations in Sally Rooney’s Normal People”. This study discussed the depiction of power relations and protagonist resists towards the power relations which occurs in novel Normal People (2018). The novel is about a loner girl named Marianne Sheridan who lived with her mother and older brother in Carricklea. She has a bad relationship with her family because her mother and older brother treat her badly and constantly abuse her verbally and physically. Moreover, she also had a complicated relationship with Connell Waldron. In conducting this study, qualitative method was used. The writer used the theory of power by Michel Foucault (2001) to analyze the power relations in the novel. The result of this study shows that the abuse that the main character experienced is the cause of the power relation. There are two ways of relations, relationship between parents and daughter, relationship between older brother and younger sister. The main character experienced verbal and physical abuse. The resistance of the protagonist towards the power relations to avoid, remain silent, and ask for help from Connell. Keywords: Abuse, Michel Foucault, Power Relations, Resistance.